Lived experiences of family members caring for a relative with mental illness - Mihloti Eunice Shimange; Marie Poggenpoel; Chris P.H. Myburgh; Nompumelelo Ntshingila (International Journal of Africa Nursing Sciences, 2022)
Background: Mental illness may cause a variety of psychosocial problems, such as decreased quality of life for the affected individual’s family members and an increased social distance for the individual and family members caring for a relative with mental illness. Purpose: To gain an understanding of the lived experiences of family members caring for a relative with mental illness in Giyani, Limpopo province. Design and Methods: A qualitative, exploratory, descriptive and contextual research design was utilised. Data were collected through in-depth individual interviews with eight participants, observations, and field notes. Data were analysed utilising Tesch’s open-coding method, and an independent coder assisted in the analysis process. Results: The results revealed that family members caring for a relative with mental illness were alert about safety aspects related to their relative with mental illness. Participants experienced that their relative was not mentally stable, as evidenced by erratic behaviour. They also experienced challenges in caring for a relative with mental illness and engaged coping strategies in caring for a relative with mental illness. Conclusion: Based on the findings from this study, it was recommended that support interventions for these families by providing mental health education, strengthening the families’ existing coping strategies, and building their resilience. The implications for practice for psychiatric nurses and stakeholders in social services were highlighted in supporting the families of relatives with mental illness.